Cardiac Pacing and Monitoring New Methods, Modern Devices - Min, Mart (IntechOpen, 2019)
Different artificial tools, such as heart-pacing devices, wearable and implantable monitors, engineered heart valves and stents, and many other cardiac devices, are in use in medical practice. Recent developments in the methods of cardiac pacing along with appropriate selection of equipment are the purpose of this book. Implantable heart rate management devices and wearable cardiac monitors are discussed. Indications for using specific types of cardiac pacemakers, cardiac resynchronization therapy devices, and implantable cardioverter defibrillators (ICDs) are of interest and their contraindications are considered. Special attention is paid to using leadless devices. The subcutaneous ICD obviates the need for transvenous leads and leadless pacemakers are entirely implantable into the right ventricle. Finally, applications of user-friendly wearable devices for the detection of atrial arrhythmia are debated.